Kompetensi Kewirausahaan Kepala Sekolah Dalam Mendorong Kesejahteraan Warga Sekolah Dasar - Kurniyanti, Wiwin; Harsono, Harsono; Fathoni, Achmad; Minsih, Minsih (Cetta: Jurnal Ilmu Pendidikan, 2025)
The principal is a component of education that has a major influence on school development. Principals have a strategic role in managing resources and building collaboration to create a more prosperous educational environment. This study was conducted with the aim of explaining the form of entrepreneurial competence of school principals in promoting the welfare of school community. This study used a qualitative approach with an educational ethnography research design. Data were collected through three ways, namely: in-depth interviews, observation, and documentation studies. Data validity testing technique using source triangulation. Data analysis in this study used data analysis techniques within the site. This research was conducted in an elementary school that utilizes dry land farming to grow vegetable crops. The results showed that entrepreneurial competence grows through the management and utilization of agricultural land and by developing social capital. The combination of these two strategies is not only a means of developing the principal's entrepreneurial competence, but also a source of additional income for the school community. The additional income can help meet operational needs and promote the welfare of the school community.